PERUBAHAN FONEM PADA ANAK USIA 2-4 TAHUN DI PAUD ANNA HUSADA JL. BRANTAS NO. 1A PERUM. CANDRA LAND MLAJAH BANGKALAN (KAJIAN FONOLOGIS) - Ria Kristia Fatmasari (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2020)
This study discusses phoneme changes in children aged 2-4 years at Anna Husada Jl. Brantas No.1A Perum Candra Land Mlajah Bangkalan. The background of the sound of language spoken by the child, namely the child when communicating often changes and obsolescence of phonemes in his speech. Several factors cause phenomenal changes in children's speech, namely lack of mastery of vocabulary, stages of language improvement, second language learning (B2), and parenting patterns. This is what causes phenomenal changes when children dialogue or speak. The method used in the collection of data in the form refer to the method of reading involved in conversational skills, record techniques and note-taking techniques. The data that has been collected is then analyzed using qualitative descriptive methods. The results of the analysis that have been found in that are, children are not always the same in the phoneme changes made, it happens because it adapts to the development, as well as the child's ability to speak. It is very important to use Indonesian properly and correctly when speaking so that children are not accustomed to making changes when speaking and there is no misinterpretation and do not become displaced Indonesian language that is good and correct in speech.